Pembelajaran Pendidikan Agama Islam Berbasis E-Learning (Studi Inovasi Pendidik MTS. PAI Medan di Tengah Wabah Covid-19) - Lubis, Masruroh; Yusri, Dairina; Gusman, Media (Fitrah: Journal of Islamic Education, 2020)
The aims of this research is: 1) the rules related to distance learning during the Covid-19 emergency period, 2) type of learning innovations applied by Islamic study teachers, 3) obstacles faced by Islamic education teachers during e-learning. This research was conducted at MTS. PAI. The research method used is a qualitative research method, with a descriptive study model. The results of the study indicate that the policies adopted in MTS. PAI during the emergency period Covid-19 is still carrying out learning, but carried out with a distance-based internet network system. This policy is always implemented in accordance with government regulations. The variety of learning innovations applied are 1) Innovation In intra curricular activities, such as the presentation of learning with multimedia. PAI learning that emphasizes the motto 'friendly'. online-based discussions and assignments, Application of project-based methods, evaluation of learning based on activities. 2) Innovations in Extracurricular activities, such as routine reading and memorizing the Koran. The obstacles faced are 1) mindset errors, 2) Lack of competence, 3) teacher and student unpreparedness in facing E-Learning learning.